Preparing Nurses for Community Health Care: A Comparative Study of the ADN and BSN Programs - Ghaffari, Masoud (International Journal of Medical and Health Sciences Research, 2018)
Because of current changes in our society and the healthcare system, it is important to be aware of the expertise and efficiency of nurses in terms of how they are prepared to meet the health care needs of our society today and in the future. Along with this awareness, it is important for us to examine carefully the manner in which nurses are educated to meet the increasing demands of a changing society and the increased need for community health care. The purpose of this study was to compare the degree to which ADN’s and BSN’s graduates, from selected schools in the Northeast region of the United States that were exposed to community health nursing concepts during their educational programs. This descriptive, non-experimental study compared the community health orientation of graduating nursing and the degree of student exposure to community health concepts in their curricula. Data analysis revealed a difference in the perceived exposure to community health nursing concepts, with BSN students perceiving greater exposure to the concepts. Also, there was a difference in the community health orientation of students, with the highest orientation demonstrated in BSN programs.